In Vitro Activity of Monofunctional Pt-II Complex Based on 8-Aminoquinoline against Human Glioblastoma - Valentina Coccè; Isabella Rimoldi; Giorgio Facchetti; Emilio Ciusani; Giulio Alessandri; Lucia Signorini; Francesca Sisto; Aldo Giannì; Francesca Paino; Augusto Pessina (Pharmaceutics, 2021)
A new cationic Pt(II) complex bearing 8-aminoquinoline as chelating ligand (called Pt-8AQ) was evaluated against two human carcinomas, one mesothelioma, and three glioblastoma cell lines. The in vitro comparison to the clinically approved CisPt showed a minor activity of Pt-8AQ against carcinoma and mesothelioma, whereas a significant activity of Pt-8AQ was observed on the proliferation of the three glioblastoma cell lines (U87-MG IC50 = 3.68 ± 0.69 µM; U373-MG IC50 = 11.53 ± 0.16 µM; U138-MG IC50 = 8.05 ± 0.23 µM) that was higher than that observed with the clinically approved CisPt (U87-MG IC50 = 7.27 + 1.80 µM; U373-MG IC50 = 22.69 ± 0.05 µM; U138-MG IC50 = 32.1 ± 4.44 µM). Cell cycle analysis proved that Pt-8AQ significantly affected the cell cycle pattern by increasing the apoptotic cells represented by the sub G0/G1 region related with a downregulation of p53 and Bcl-2. Moreover, an NMR investigation of Pt-8AQ interaction with 9-EtG, GSH, and Mets7 excluded DNA as the main target, suggesting a novel mechanism of action. Our study demonstrated the high stability of Pt-8AQ after incubation at 37 °C and a significant antineoplastic activity on glioblastomas. These features also make Pt-8AQ a good candidate for developing a new selective advanced cell chemotherapy approach in combination with MSCs.